Study of Thermomechanical Properties of an Al-Zn-Based Composite Reinforced with Dodecaboride Particles. (14th February 2018) - Colón Quintana, José Luis; Soto Medina, Sujeily; Hernández, Marivic; Suárez, Oscar Marcelo
Abstract : The effect of the addition of AlB 12 particles to gravity cast Al-Zn alloys was studied and related to the composite deformation at high temperature. The characterization techniques of choice were thermomechanical analysis (TMA), Brinell hardness (HB), and optical microscopy. After homogenization treatment, Al-5 wt.% Zn and Al-10 wt.% Zn with 0, 2.08, 4.16 wt.% B samples were quenched in ice water and tested using a thermomechanical analyzer at different temperatures. It was found that after TMA treatment, Brinell hardness of the composites increased for higher concentrations of zinc and AlB 12 particles, as expected. Such increment was not, however, uniform for all samples at higher temperature levels, suggesting a nonequilibrium interaction between reinforcing particles and zinc. This was further corroborated by TMA experiments, which revealed that for samples with Al-10 wt.% Zn, high temperature deformation augmented as more AlB 12 particles were present. After high temperature treatment, precipitation of zinc-rich allotriomorphs was observed by the optical microscopy performed on the samples near or on the aluminum grain boundaries, which discarded the potential effect of fine precipitation due to aging.